PENGARUH INTELLECTUAL CAPITAL DAN ESG TERHADAP MANAJEMEN LABA YANG DIMODERASI OLEH PROFITABILITAS - Novita Andriani; Regina Jansen Arsjah (Jurnal Ekonomi Trisakti, 2022)
This study aims to examine and analyze the effect of intellectual capital dan environmental, social, and governance on earnings management with profitability as a moderating variable. This research is quantitative research using secondary data. The population in this study are manufacturing and banking companies listed on the Indonesia Stock Exchange (IDX) in 2018 – 2020 period. The sample of this study amounted to 93 companies obtained by purposive sampling method. The data analysis method used is panel data regression analysis. Statistic tool used is e-views. The results of this study are intellectual capital and ESG has a negative effect on earnings management, profitability can strengthen the negative effect of intellectual capital and ESG on earnings management.